A scientific approach to writing for engineers and scientists - Berger, Robert E. (IEEE PCS professional engineering communication series, 2014)
"This book is a guide to technical writing, presented in a systematic framework that mirrors the logic associated with the scientific process itself. Other English books merely define concepts and provide rules; this one explains the reasoning behind the rules. Other writing books for scientists and engineers focus primarily on how to gather and organize materials; this one focuses primarily on how to compose a readable sentence. The approach should be satisfying not only to scientists and engineers, but also to anyone who once took a grammar course but can't remember the rules--because there was no exposure to underlying principles"--